Desynchronized circadian clock and exposures to xenobiotics are associated with differentiated disease phenotypes: The interface of desynchronized circadian clock and exposures to xenobiotics would lead to adverse response and recovery - Makris, Konstantinos C. (My University, 2021)
A paradigm shift in the human chronotoxicity of xenobiotics would study two-sided desynchronized phenomena of interfacial interactions between cyclic or periodic environmental insults and the endogenous response and recovery profile. These systems-based networks are under the influence of well-synchronized biological clocks and their metabolic regulators. This perspective argues in favor of addressing the concept of synchronization in studies involving critical life windows of susceptibility, or circadian rhythms, or 24-hour (periodic) diurnal rhythms and answering whether these disruptions in synchronization would affect response and recovery or disease phenotypes associated with environmental insults, e.g., xenobiotics. Synchronization or synchrony is defined as the totality of elements that appear during the same time period within a system, including the network of interactions between the system's elements. Desynchronized interfaces during critical life windows or in time-repeated exposure events would likely lead to initiating a cascade of adverse health effects associated with differentiated disease phenotypes.
Keywords: Chronobiology; Chronotoxicology; Circadian; Critical life stage; Diurnal; Exposome; Public health; Synchronization